2016
DOI: 10.1210/en.2015-1685
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Vitamin D Receptor Expression and Direct Effects of 1α,25(OH)2D3 in Human Skeletal Muscle Precursor Cells

Abstract: Presence of the vitamin D receptor and direct effects of vitamin D on the proliferation and differentiation of muscle precursor cells have been demonstrated in animal models. However, the effects and mechanisms of vitamin D actions in human skeletal muscle, and the presence of the vitamin D receptor in human adult skeletal muscle, remain to be established. Here, we investigated the role of vitamin D in human muscle cells at various stages of differentiation. We demonstrate that the components of the vitamin D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
149
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(158 citation statements)
references
References 40 publications
9
149
0
Order By: Relevance
“…4c). Indeed, Myostatin mRNA levels were reported to be unaltered in human muscle precursor cells upon 1α,25(OH) 2 D 3 treatment [14], suggesting that the modulation of Myostatin in VDR −/− muscles might be confined to the fiber alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4c). Indeed, Myostatin mRNA levels were reported to be unaltered in human muscle precursor cells upon 1α,25(OH) 2 D 3 treatment [14], suggesting that the modulation of Myostatin in VDR −/− muscles might be confined to the fiber alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, signaling pathways that link the aberrations in myogenic gene expression and the progressive muscle atrophy observed postnatally in VDR −/− muscles have been unexplored. More importantly, recent evidence indicates that components of the vitamin D signaling cascade are expressed in human precursor cells and that the VDR in rodent quadriceps muscle responds to 1α,25(OH) 2 D 3 treatment [14, 15]. Nevertheless, mechanistic studies that account for the muscle atrophy observed in vitamin D-deficient individuals are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, clinical signs of severe 25(OH)D deficiency (<25 nmol/L) [10] have been linked to myopathy, muscle pain and impaired gait, with amelioration by vitamin D supplementation [9]. Secondly, several studies have localised vitamin D receptor (VDR) in human muscle cell lines, myoblasts [11], and adult skeletal muscle [12,13], although opposing views have been published [14]. Thirdly, functional in vitro studies, have provided insights into the direct biological role of the active form of 25(OH)D, 1,25(OH2)D in regulation of genes and signalling pathways affecting calcium homeostasis, proliferation and differentiation of muscle cells [9], and positive correlation between 25(OH)D 3 and expression of 24 muscle genes at the mRNA level [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Al-Eisa et al evidenced a correlation between higher serum vitamin D levels and better physical muscle performance in physically active healthy older adults, probably by regulate on of the biosynthesis of creatine kinase, lactic acid dehydrogenase, troponin I, and hydroxyproline (AlEisa et al, 2016). Moreover, vitamin D receptor gene expression could have a role in muscle function, with a possible effect of this vitamin on proliferation and differentiation of muscle precursors (Bozsodi et al, 2016, Olsson et al, 2016. Some studies on the effect of this gene's variants on muscle strength are still contradictory, but individual genetic patterns might explain the inconsistency of our results on the association between vitamin D and muscle function (Bozsodi et al, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…Recent studies hypothesized a negative effect of vitamin D deficit on the structure and function of the neuromuscular junction, causing lack of a stress response in muscles (Gifondorwa et al, 2016). Moreover, the vitamin D receptor gene has been indicated as a possible candidate gene in muscle function (Bozsodi et al, 2016;Olsson et al, 2016). The aims of this study were: i) to compare vitamin D blood levels in ALS patients with healthy subjects; ii) to correlate vitamin D blood levels with clinical and respiratory functions in enrolled patients; iii) to evaluate whether administration of vitamin D could modify the clinical progression of the disease.…”
Section: Introductionmentioning
confidence: 99%